OP0002 Tofacitinib in Patients with Ankylosing Spondylitis: A Phase 2, 16-Week, Randomised, Placebo-Controlled, Dose-Ranging Study. (15th July 2016) - van der Heijde, D.; Deodhar, A.; Wei, J.C.; Drescher, E.; Fleishaker, D.; Hendrikx, T.; Li, D.; Menon, S.; Kanik, K.
Abstract : Background: Tofacitinib is an oral JAK inhibitor that has been investigated for the treatment of ankylosing spondylitis (AS). Objectives: To investigate for the first time the effects of tofacitinib in adult patients (pts) with active AS. Methods: This was a 16-week (wk), Phase 2, multicentre, randomised, double-blind, placebo (PBO)-controlled, dose-ranging study (NCT01786668 ) to investigate efficacy, safety and dose-response of tofacitinib in pts with AS. Pts fulfilling the modified New York criteria (central read) were randomised 1:1:1:1 to PBO or tofacitinib 2, 5 or 10 mg BID for 12 wks plus 4 wks follow-up. Primary efficacy endpoint was ASAS20 response rate at Wk 12 using a 3-parameter Bayesian E max model by assuming a monotonic response. Secondary endpoints included ASAS40 response rate, AS disease activity score using C-reactive protein (ASDAS), Bath AS disease activity index 50% (BASDAI50) response rate, Bath AS functional index, Bath AS metrology index (linear method), Spondyloarthritis Research Consortium of Canada (SPARCC) score of sacroiliac (SI) joints and spine. Safety endpoints included adverse events (AEs) and laboratory outcomes. Results: 208 pts were randomised and 207 treated; 196 pts completed the study. 51 pts (PBO group) and 52 (each tofacitinib group) were included in analyses. Baseline demographics and disease characteristics were balanced between groups and typical of AS populations (87.4% HLA-B27 positive; 81.2% white; 69.1% male; mean age 42 years; mean disease duration 6.3 years; mean BASDAI 6.7). The table summarises safety and efficacy results. The ASAS20 E max model showed tofacitinib 10 mg BID had a high response rate and its confidence bounds met a pre-specified efficacy decision rule. ASAS20 response rates by NRI were significantly greater with tofacitinib 5 mg BID vs PBO, compared with 2 or 10 mg BID. All tofacitinib groups had ASAS40, ASDAS and BASDAI50 improvements of similar magnitude vs PBO. Tofacitinib 2 mg BID did not differ vs PBO in remaining clinical efficacy measures or SPARCC scores. Tofacitinib 5 and 10 mg BID had greater clinical efficacy vs PBO, with minimal differences between doses, and significantly improved SPARCC SI joint and spine scores vs PBO. No tofacitinib-related safety issues unique to the AS population or new safety concerns were identified. Two treatment-related herpes zoster cases were reported (1 each with tofacitinib 2 and 10 mg BID). No cases of tuberculosis, malignancy, gastrointestinal perforation or death were reported. Dose-dependent changes in laboratory outcomes commonly reported in other tofacitinib studies were observed and returned to approximately baseline values by Wk 16. Conclusions: Tofacitinib 5 and 10 mg BID demonstrated greater clinical and imaging efficacy vs PBO in reducing the signs and symptoms of AS in adults with active AS. Safety was similar to that reported for tofacitinib studies in other indications. Acknowledgement: Previously presented (van der Heijde D et al. Arthritis Rheumatol 2015; 67(S10): Abstr 5L) and reproduced with permission from Arthritis Rheumatol. This study was funded by Pfizer Inc. Editorial support was provided by S Johnson of CMC and funded by Pfizer Inc. Disclosure of Interest: D. van der Heijde Consultant for: AbbVie, Amgen, AstraZeneca, Augurex, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Centocor, Chugai, Covagen, Daiichi, Eli Lilly, Galapagos, GlaxoSmithKline, Janssen Biologics, Merck, Novartis, Novo Nordisk, Otsuka, Pfizer Inc, Roche, Sanofi-Aventis, UCB, Vertex, A. Deodhar Grant/research support from: AbbVie, Amgen, Eli Lilly, Janssen, Novartis, Pfizer Inc, and UCB, Consultant for: AbbVie, Amgen, Boehringer Ingelheim, Janssen, Novartis, Pfizer Inc, and UCB, J. Wei Grant/research support from: AbbVie, Bristol-Myers Squibb, Celgene, Chugai, Eisai, Janssen, Novartis, Pfizer Inc, Sanofi-Aventis, TSH Taiwan, and UCB, Consultant for: AbbVie, Bristol-Myers Squibb, Celgene, Chugai, Eisai, Janssen, Novartis, Pfizer Inc, Sanofi-Aventis, TSH Taiwan, and UCB, E. Drescher Grant/research support from: AbbVie, Bristol-Myers Squibb, Celgene, Pfizer Inc, Novartis, UCB, Amgen, Lilly, and Sanofi-Aventis, D. Fleishaker Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, T. Hendrikx Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, D. Li Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Menon Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, K. Kanik Shareholder of: Pfizer Inc, Employee of: Pfizer Inc